Repetitive Restricted Behaviors in Autism Spectrum Disorder: From Mechanism to Development of Therapeutics - Tian, Junbin; Gao, Xuping; Yang, Li (Frontiers in Neuroscience, 2022)
Autism spectrum disorder (ASD) is a common neurodevelopmental disorder with social communication impairments and repetitive restricted behaviors (RRBs), which is usually detected in early childhood. RRBs are purposeless patterns of behavior and interfere with normal behaviors. To date, there is no specific definition or generally acknowledged assessment tools for RRBs. Understanding the mechanisms of RRBs in ASD children, such as the neural circuit alterations, neuropsychological changes, and abnormal immune functions, may play an important role in finding new targeting therapeutics. Although the treatment of RRBs has become a major issue in ASD management, evidence about medication for RRBs is limited, and behavioral intervention remains the most effective and safe strategy. Emerging treatment options (e.g., supplementary and cell therapy) for RRBs are at early research stage. Here we reviewed the latest progress of RRBs from mechanism to therapeutics, and proposed the potential future directions in RRBs research.